Al Mar’atus Shalihah dalam Penerapan Nilai-nilai Islam (Studi Kasus di Desa Aek Sitio-Tio Kec. Pandan Kab. Tapanuli Tengah - Zega, Aisyiyah; Damanik, Nurliana (Lembaga Yasin AlSys, 2024)
A woman who consistently obeys Allah's instructions and abstains from His prohibitions is known as an Al Mar'atus shalihah or shalihah woman. She will naturally obey Allah's Messenger if she obeys Him, which will give her moral responsibility and a significant position in communal life. A group of morally upright women who uphold and defend their honor and self-worth is known as Al Mar'atus shalihah. The purpose of this study is to ascertain Mar'atus Shalihah's true standing with regard to the implementation of Islamic principles in the town of Aek Sitio-tio. The method used in this study is descriptive qualitative. Research that describes an item, situation, or social context and will be expounded upon in narrative writing is classified as descriptive research. The findings that the investigator discovered were the aqidah, sharia, and moral standards of Islam that are effectively enforced by the mar'atus shalihah, a group of women and teens in the village of Aek Sitio-tio, Pandan District, Kab. Central Tapanuli because village officials and community leaders are also involved in the program to form these values, especially aqidah values. Various factors influence how the formation of mar'atus shalihah in the application of these three values. However, there are still some who unknowingly violate Islamic values and do not apply them properly and correctly because village officials and community leaders are also involved in the program to form these values, especially aqidah values. Various factors influence how the formation of mar'atus shalihah in the application of these three values. However, there are still some who unknowingly violate Islamic values and do not apply them properly and correctly.